Components of the metabolic syndrome in girls with Turner syndrome treated with growth hormone in a long term prospective study - Błaszczyk, Ewa; Shulhai, Anna-Mariia; Gieburowska, Joanna; Barański, Kamil; Gawlik, Aneta Monika (Frontiers in Endocrinology, 2023)
Background: Components of the metabolic syndrome are more common in patients with Turner syndrome (TS) than in the general population. Long-term growth hormone (GH) treatment also affects the parameters of carbohydrate metabolism. Therefore, all these factors should be monitored in girls with TS.Objective: To assess the occurrence of metabolic syndrome components in TS girls before GH treatment and to monitor changes in metabolic parameters throughout GH therapy.Patients and Method: 89 TS patients were enrolled in the study. Clinical and laboratory data after the 1st (V1), 3rd (V3), 5th (V5) and 10th (V10) year of GH therapy was available respectively in 60, 76, 50 and 22 patients. The patients' biochemical phenotypes were determined by glucose 0', 120', insulin 0', 120', HOMA-IR, Ins/Glu ratio, HDL-cholesterol and triglycerides (TG) concentration.Results: Obesity was found during V0 in 7.9% of patients ,V1 -5%, V3 -3.9%, V5 -2%, V10 -0%.No patient met diagnostic criteria for diabetes. A significant increase in the basal plasma glucose 0' was found in the first five years of therapy (pV0-V1<0.001; pV0-V3=0.006; pV0-V5<0.001). V10 glucose 120' values were significantly lower than at the onset of GH treatment (pV0-V10=0.046). The serum insulin 0' and 120' concentrations as well as insulin resistance increased during treatment. No statistically significant differences in serum TG and HDL-cholesterol levels during GH therapy were found.The development of insulin resistance and carbohydrate metabolism impairment have the greatest manifestations during GH therapy in girls with TS. Monitoring the basic parameters of carbohydrate-lipid metabolism in girls with TS seems particularly important.